THE CONTRIBUTION OF THE FISHERIES SUB-SECTOR REGIONAL GROSS DOMESTIC PRODUCT (GDP) AT DISTRICT OF MERANTI ISLANDS IN RIAU PROVINCE - Rostar, Muhendar; Bathara, Lamun; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on October 2013 was, held at District of Meranti Islands in Riau Province. The research location was determined intentionally (purposive) and the method that used was a survey by analyzing secondary data, researcher used the time series data from 2008 to 2012. The purpose of this research was to determine the contribution of the fisheries sub-sector regional gross domestic product (GDP), to know the base and non-base fisheries sub-sector, determine the impact of fisheries sub-sector of the regional income and employment of District of Meranti Islands in Riau Province.Fisheries sub-sector consists of the catching, aquaculture and processing. The results of the fisheries sub-sector contributing on 2008 to 2011 has increased from 3.89% to 4.11%, meanwhile in 2011 to 2012 has decreased to 4.09%. Based on the results of Locationt Quetient (LQ) sub-sector of the fishery in 2008-2012 is sector basis with LQ values ranged from 2.67 to 2.90. The result of the multiplier effect of the fisheries sub-sector 2009- 2012 ranged from 18.49 up to 25.49.